UPAYA MENINGKATKAN AKURASI SHOOTING MENGGUNAKAN MEDIA GAWANG MINI PADA SEPAKBOLA DI EKSTAKULIKULER SMPN 3 JATIBARANG - Yudha Nazmul Fasha; Rahmat Iqbal; Abdul Salam Hidayat (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to find out how much influence shooting training using mini goal media has on basic shooting techniques in extracurricular football at SMP Negeri 3 Jatibarang. This research uses an experimental method with a One Group PretestPosttest research design with a population of 18 football extracurricular members/students. The sampling technique used in this research used total sampling. This research instrument uses a basic shooting technique test instrument with the average results before being given treatment and after being given treatment experiencing a significant increase, namely the pretest mean of 23.78 and the posttest mean of 33.00. Based on the calculation results of the hypothesis test, the Paired Sample T Test with the data obtained from the results of this research, the significance (2-tailed) is 0.000 < 0.05, This means that there is an influence from the use of mini goal media on basic shooting technical skills in extracurricular soccer games for members of SMP Negeri 3 Jatibarang.